Synthesis of 5-arylidene-3-(pyridin-4-yl)-2-thio-imidazolidinone derivatives with the end of flexible chain modified with aryl groups under microwave. Issue 5 (4th March 2022) - Mao, Chongyang; Cao, Zhen; Fu, Boqiao; Wang, Shengcheng; Chen, Haowei; Xia, Caifen; Hu, Xinliang; Huang, Xinyuan; Qin, Caiqin
Abstract: A series of 2-thio-imidazolidinone derivatives with aryl group modifications at the end of the five-carbon side chain were synthesized. Compared with conventional heating, the target compounds were obtained in higher yield (77–95%) and shorter reaction time under the assistance of microwave heating 100 °C over 2 h. Graphical Abstract: UF0001